Increased physical activity frequency in primary school adolescents is related to reduced risk of self-reported adverse mental health symptoms - Chunmei Li; Xiong-Zhe Han (Frontiers in Public Health)
PurposeThe sedentary lifestyle and mental health issues of primary school students are major public health issues in China and globally. Some studies have shown that regular physical activity is beneficial to health, but there are few epidemiological investigations on the relationship between physical activity and psychological problems. The purpose of this study is to explore the relationship between physical activity and mental health.Materials and methodsWe used data from our study, which was based on the Yanbian University School of Physical Education health survey of primary education, in which 822 elementary school students in grades 4–6 participated. Physical activity is evaluated through three questions (intensity, frequency, and duration), and mental health issues are evaluated through SPSS.ResultsIn our study, 488 primary school students (200 males and 288 females) participated and completed self-reported data on physical activity and mental health variables. The findings revealed that a higher frequency of physical activity was significantly associated with decreased risks of various mental health symptoms. Specifically, students who reported a higher frequency of physical activity exhibited a lower risk of depressive symptoms (RR = 0.31, 95% CI = 0.14–0.71, p < 0.05), anxiety (RR = 0.35, 95% CI = 0.18–0.67, p < 0.05), low self-esteem (RR = 0.48, 95% CI = 0.26–0.90, p < 0.05), and life dissatisfaction (RR = 0.58, 95% CI = 0.35–0.96, p < 0.05). The risk of somatic complaints reporting was slightly lesser if the prevalence of physical activity reported at screening was higher (RR = 0.93, 95% CI = 0.50–1.76), although this result was not statistically significant (p > 0.05). These findings highlight the importance of regular physical activity in promoting mental health among primary school students.ConclusionGiven the dose–response relationship between poor mental health and lack of physical activity, it is necessary to actively promote primary school students to participate more actively in physical activities.